Feasibility of a far infrared laser based polarimeter diagnostic system for the JT-60SA fusion experiment. (8th June 2018) - Boboc, A; Gil, C; Terranova, D; Orsitto, F P; Soare, S; Lotte, P; Sozzi, C; Imazawa, R; Kubo, H
Abstract: JT-60SA is the large Tokamak device that is being built in Japan under the Broader Approach Satellite Tokamak Programme and the Japanese National Programme and will operate as a satellite machine for ITER. The main goal of the JT-60SA Programme is to provide valuable information for the ITER steady-state scenario and for the design of DEMO, where the real-time control of the safety factor profile is very important, in connection with both MHD stability and plasma confinement. It has been demonstrated in this work that to this end polarimetry measurements are necessary, in particular in order to reconstruct the safety factor profile in reversed shear scenarios. In this paper we present the main steps of a conceptual feasibility study of a multi-channel polarimeter diagnostic and the resulting optimised geometry. In this study, magnetic scenario modelling, a realistic CAD-driven design and long-term operation requirements, rarely even considered at this stage, have been considered. It is shown that a far infrared polarimeter system, with a laser operating at a wavelength of 194.7 μ m and up to twelve channels can be envisaged for JT-60SA. The top requirements can be attained, i.e., that the polarimeter, together with other diagnostic measurements, should provide q-profile reconstruction with an accuracy of 10% for the entire plasma cycle and suitable time resolution for real-time applications, in particular in high density and ITER-relevant plasma scenarios.